Identity formation: An auto-ethnography of Indonesian student becomes a legitimate speaker and teacher of English - Rina Febriani Sarie; Bambang Widi Pratolo; Eko Purwanti (Institute of Advanced Engineering and Science, 2020)
Several studies have investigated how the TESOL program influenced the construction of Non-Native English Speaker Teachers’ identities, yet few literature concerns about the negotiation of NNESTs’ identity as legitimate speakers and teachers of English. This paper was an auto-ethnographic investigation of my personal experience as one of international students in the TESOL program at an Australian university. Drawing on Norton’s theory of language and identity, this study examined a complex process of my identity formation as a legitimate speaker and teacher of English after studying one of a critical pedagogical unit ‘Language, Culture, and Curriculum’. The findings revealed that the TESOL program enabled me to discover and explore another part of myself as a legitimate speaker and teacher of English through linguistic constructs and rich knowledge given in that unit. It also supported that a critical pedagogical unit could empower international students to form their identities as confident and professional English teachers back to their countries.